2021
DOI: 10.1111/1462-2920.15648
|View full text |Cite
|
Sign up to set email alerts
|

Lytic polysaccharide monooxygenases promote oxidative cleavage of lignin and lignin–carbohydrate complexes during fungal degradation of lignocellulose

Abstract: Summary Overcoming lignocellulosic biomass recalcitrance, especially the cleavage of cross‐linkages in lignin–carbohydrate complexes (LCCs) and lignin, is essential for both the carbon cycle and industrial biorefinery. Lytic polysaccharide monooxygenases (LPMOs) are copper‐containing enzymes that play a key role in fungal polysaccharide oxidative degradation. Nevertheless, comprehensive analysis showed that LPMOs from a white‐rot fungus, Pleurotus ostreatus, correlated well with the Fenton reaction and were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Cotton stalks are less expensive than other lignocellulosic materials and are therefore a highly desirable lignocellulosic material. However, lignocellulosic material contains lignin, a highly irregular and insoluble polymer that is covalently linked with hemicellulose and cellulose, making it difficult to be directly utilized in the biological transformation process ( Xing et al, 2018 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cotton stalks are less expensive than other lignocellulosic materials and are therefore a highly desirable lignocellulosic material. However, lignocellulosic material contains lignin, a highly irregular and insoluble polymer that is covalently linked with hemicellulose and cellulose, making it difficult to be directly utilized in the biological transformation process ( Xing et al, 2018 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Ca 2+ could increase the IDET rate in CDH, , while the enhancement of CDH cyt c reduction activity by Mn 2+ has not been reported. Recently, it was discovered that Mn 2+ addition changed the extracellular enzyme expression profiles of the fungi (e.g., H 2 O 2 -generating enzymes and LPMOs were increased) and reduced the biomass recalcitrance through C α -oxidation cleavage of β-O-4 ether linkages, leading to more efficient deconstruction of lignocellulose by white-rot fungi. Therefore, besides Ca 2+ , we also evaluated the effect of Mn 2+ on the CDH-LPMO system due to its potential role in the degradation of lignocellulose.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Li et al. [ 97 ] compared the degradation effect of Pleurotus ostreatus haucc 162 with and without Mn 2+ , and the results showed that the presence of Mn 2+ enhanced the depolymerization of lignin and significantly damaged the crosslinking structure. After the addition of Mn 2+ , the contents of polysaccharide monooxygenase and 1,4-benzoquinone reductase were increased, which played a significant role in the driving of Fenton reaction.…”
Section: Methods For Improving Processmentioning
confidence: 99%